Case reports Lichen sclerosus mimicking Bowen’s disease - Rotsztejn, Helena; Trznadel-Grodzka, Ewa; Krawczyk, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Lichen sclerosus (LS) is a chronic inflammatory skin disease of unclear etiology in which lymphocytes play an important role. There is some evidence that LS is an autoimmune disease. The lesions are observed on mucosa areas in many cases in women genital region and on the skin of any part of the body. We report a case of a 54-year-old man. The single, inflamed lesion was situated in the scapula area of the back. It was clinically diagnosed as Bowen’s disease. A significant improvement was observed after treatment with clobederm ointment.